Abstracts (Edited by Prof. Tahir Mahmood) - Mahmood, Tahir (Pakistan Journal of Ophthalmology, 2009)
Factors affecting outcome of punctoplasty surgery: a review of 205 cases Shahid H, Sandhu A, Keenan T, Pearson A Br J Ophthaimol 2008; 92: 1689-92 Changes in corneal wavefront aberrations in microincision and small-incision cataract surgery Tong N, He JC, Lu F, Wang Q, Qu J, Zhao YE J Cataract Refract Surg. 2008; 34:2085-90 Higher-order aberrations induced by nuclear cataract Lee J, Kim MJ, Tchah H J Cataract Refract Surg. 2008; 4: 2104-9 Estimation of the effective lens position using a rotating Scheimpflug camera Ho JD, Liou SW, Tsai RJF, MD, Tsai CY J Cataract Refract Surg. 2008; 34: 2119-27